Crevasse and rift detection in Antarctica from TerraSAR-X satellite imagery - Marsh, O.J.; Price, D.; Courville, Z.R.; Floricioiu, Dana (Cold Regions Science and Technology, 2021)
Surface crevasses covered by snow bridges can be mapped remotely on ice sheets and glaciers using active microwave synthetic aperture radar. They are highlighted against the surrounding snow due to increased scattering from the side-walls and base of snow bridges and usually appear as linear features. The contrast between crevasses and crevasse-free regions depends on the design of the sensor, the image acquisition parameters and the properties of the snow. Here we quantify how crevassed regions are represented at X-band for different polarizations, look directions and incidence angles, and discuss whether additional information about their physical properties can be gained from their radar signature. Snow bridge thicknesses and crevasse widths are measured on the ground in the McMurdo Shear Zone and Brunt Ice Shelf by ground-penetrating radar and excavation. TerraSAR-X is shown to reliably distinguish crevasse location, balancing penetration into the snow and horizontal resolution. We provide recommendations for radar imaging parameters that optimize the identification of individual crevasses and crevassed regions.